ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Pada SKPD Badan Lingkungan Hidup Provinsi Sumatera Utara) - Mirwansyah Putra Ritonga (JURNAL ILMIAH MAKSITEK, 2018)
The objective of the research was to analyze the factors which influence managerial performance with work motivation as intervening variable at SKPD (Regional Work Unit) in North Sumatera Provincial Administration. The population was 135 government employees at SKPD of Environmental Agency of North Sumatera Province. The research used a survey or census method in which the whole population was used as the samples. Primary data were respondents’ answers of the questionnaires. F-test, t-test and direct and indurect influence were used for hypothesis test. The result of the research showed that, simultaneously, there was significant influence of budget participation, paternalistic culture, organizational commitment, leadership style, and work ethics on work motivation. Partially, budget participation had positive but insignificant influence on managerial performance, paternalistic culture had positive but insiginifanct influence on managerial performance, leadership style had positive but insignificant influence on managerial performance, and work ethics had positive and significant influence on managerial performance. Meanwhile, budget participation had positive but insignificant influence on work motivation, paternalistic culture had positive but insignificant influence on work motivation, organizational commitment had positive and significant influence on work motivation, leadership style had positive and significant influenced on work motivaton, work ethics had positive but insignificant influence on work motivation, and motivation had positive and significant influence on managerial performance. The result of path analysis showed that work motivation was not an intervening variable in the correlation of budget participation, paternalistic culture, organizational commitment, leadership style, and work ethics with managerial performance.